Image-based study of marginal bone loss in teeth restored with cast endodontic posts - Sandro Luiz FARIAS; Milena Bortolloto Felippe SILVA; Rielson José Alves CARDOSO; Marcelo SPERANDIO (Faculdade São Leopoldo Mandic, 2018)
The aim of this study was to assess marginal bone loss in teeth restored with endodontic posts on all four aspects of the teeth using cone beam tomography. Bone loss was assessed via scores (0-5) in relation to root length and bone height. The results showed that the scores for the contralateral and restored sides, respectively, ranged from 0 to 3 and 0 to 5 buccally, 0 to 4 and 0 to 4 palatally, 0 to 3 and 0 and 4 mesially and 0 to 3 and 0 to 4 distally. A significant difference in bone loss was observed between the post-restored teeth and their contralaterals for the buccal, lingual/palatal and mesial aspects (p<0.05), with teeth bearing endodontic posts scoring highest. In conclusion, marginal bone loss was higher in teeth restored with intra-canal posts when compared to their sound contralaterals.